Human papillomavirus correlates of high grade cervical dysplasia among HIV-Infected women at a major treatment centre in Nigeria: a cross-sectional study (2019)
Introduction: persistent high-risk HPV (hrHPV) infection is higher among women living with HIV/AIDS thus increasing their risk for cervical cancer. We evaluated the virological and immunological correlates of cervical dysplasia in HIV-infected women. Methods: a cohort of 220 consenting women attending the antiretroviral clinic of the Federal Medical Centre, Keffi, Nigeria was tested for cervical human papilloma virus (HPV) infection using PCR. The prevalent HPV genotypes were determined by DNA sequencing. CD4+T count and type specific HPV was correlated with cervical cytology. Descriptive and inferential statistical analysis of the data was done using the statistical package for social sciences (SPSS) version 20 (SPSS Inc, Illinois, USA) for analysis after validation. Results: overall HPV prevalence was 54.1% while the hrHPV prevalence was 35.9%. Premalignant and malignant lesions were observed among participants with CD4+T counts between 200-300/mm3. A statistically significant association was observed between cervical premalignant lesions and CD4+ count (X2=24.747, P value=0.001) as well as hrHPV infections (X2=46.800, P<0.001). Conclusion: risk stratification with HPV screening among HIV-infected women will help in early case management of cervical precancerous lesions.